Konsep Pendidikan Ahlak (Takhallaqu Bi Akhlaqillah) Sebagai Proses dan Tujuan Pendidikan Islam - Yosef Farhan; Adang Hambali; Hasan Basri (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
This study aims to describe the results of a study on the concept of "takhallaqu bi akhlaqillah" as a process and goal of Islamic education. To describe these objectives, a qualitative research approach and library research methods are used. Study materials in the form of books, journal articles, and other research results are collected, classified, reduced and analyzed to obtain conclusions. The results of the study found that "takhallaqu bi akhlaqillah" which implies behaving and behaving in accordance with the teachings and moral values emphasized in Islam is a reference for the process and goals of Islamic education. The Prophet Muhammad SAW, who was expressly stated to have Al-Quran morals and noble character, was a role model or uswah hasanah for the Muslim community and by following him every Muslim or Muslim community has had the morals of the Koran and has incarnated uluhiyah qualities in daily life a day for a happy, meaningful, rewarding life